Find expert answers and community support for all your questions on IDNLearn.com. Our experts provide prompt and accurate answers to help you make informed decisions on any topic.
Sagot :
Let's break down the problem step-by-step given the polynomials [tex]\(A, B,\)[/tex] and [tex]\(C\)[/tex]:
1. Define the polynomials:
[tex]\[ A = x^2 \][/tex]
[tex]\[ B = 3x + 2 \][/tex]
[tex]\[ C = x - 3 \][/tex]
2. Compute [tex]\(AB\)[/tex]:
[tex]\[ AB = A \cdot B = x^2 \cdot (3x + 2) \][/tex]
We distribute [tex]\(x^2\)[/tex] across each term inside the parentheses:
[tex]\[ AB = x^2 \cdot 3x + x^2 \cdot 2 = 3x^3 + 2x^2 \][/tex]
3. Compute [tex]\(C^2\)[/tex]:
[tex]\[ C^2 = (x - 3)^2 \][/tex]
We use the formula [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]:
[tex]\[ C^2 = x^2 - 2 \cdot x \cdot 3 + 3^2 = x^2 - 6x + 9 \][/tex]
4. Subtract [tex]\(C^2\)[/tex] from [tex]\(AB\)[/tex]:
[tex]\[ AB - C^2 = (3x^3 + 2x^2) - (x^2 - 6x + 9) \][/tex]
Distribute the negative sign and combine like terms:
[tex]\[ AB - C^2 = 3x^3 + 2x^2 - x^2 + 6x - 9 \][/tex]
Simplify:
[tex]\[ AB - C^2 = 3x^3 + (2x^2 - x^2) + 6x - 9 = 3x^3 + x^2 + 6x - 9 \][/tex]
So, the expression [tex]\(AB - C^2\)[/tex] in simplest form is:
[tex]\[ 3x^3 + x^2 + 6x - 9 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{3 x^3 + x^2 + 6 x - 9} \][/tex]
1. Define the polynomials:
[tex]\[ A = x^2 \][/tex]
[tex]\[ B = 3x + 2 \][/tex]
[tex]\[ C = x - 3 \][/tex]
2. Compute [tex]\(AB\)[/tex]:
[tex]\[ AB = A \cdot B = x^2 \cdot (3x + 2) \][/tex]
We distribute [tex]\(x^2\)[/tex] across each term inside the parentheses:
[tex]\[ AB = x^2 \cdot 3x + x^2 \cdot 2 = 3x^3 + 2x^2 \][/tex]
3. Compute [tex]\(C^2\)[/tex]:
[tex]\[ C^2 = (x - 3)^2 \][/tex]
We use the formula [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]:
[tex]\[ C^2 = x^2 - 2 \cdot x \cdot 3 + 3^2 = x^2 - 6x + 9 \][/tex]
4. Subtract [tex]\(C^2\)[/tex] from [tex]\(AB\)[/tex]:
[tex]\[ AB - C^2 = (3x^3 + 2x^2) - (x^2 - 6x + 9) \][/tex]
Distribute the negative sign and combine like terms:
[tex]\[ AB - C^2 = 3x^3 + 2x^2 - x^2 + 6x - 9 \][/tex]
Simplify:
[tex]\[ AB - C^2 = 3x^3 + (2x^2 - x^2) + 6x - 9 = 3x^3 + x^2 + 6x - 9 \][/tex]
So, the expression [tex]\(AB - C^2\)[/tex] in simplest form is:
[tex]\[ 3x^3 + x^2 + 6x - 9 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{3 x^3 + x^2 + 6 x - 9} \][/tex]
Thank you for using this platform to share and learn. Don't hesitate to keep asking and answering. We value every contribution you make. Find precise solutions at IDNLearn.com. Thank you for trusting us with your queries, and we hope to see you again.